Effect of Petiveria alliacea leaf extract and its active components on heart muscle cell apoptosis induced by hyperglycemia - Nurmawati Fatimah; Sri Agus Sudjarwo; Arifa Mustika; Suharjono Suharjono; Jusak Nugraha; Hari Basuki Notobroto; Rochmah Kurnijasanti; Reny I'tishom; Wibi Riawan; Alphania Rahniayu (Open Veterinary Journal)
Background: Hyperglycemia is a condition in which blood sugar levels increase excessively due to a variety of factors, one of which is the body's inability to regulate insulin properly. Diabetes closely relates to this condition, which significantly contributes to premature death and disability. Long-term diabetes treatment accompanied by a strict diet provides real results in controlling blood glucose levels but can cause side effects. Therefore, it is necessary to conduct research on the potential for new drug sources with minimal side effects. Traditional medicine empirically uses the plant Petiveria alliacea.